Proceedings of the 2017 Conference on Empirical Methods in Natural Language Processing 2017
DOI: 10.18653/v1/d17-1176
|View full text |Cite
|
Sign up to set email alerts
|

Dependency Grammar Induction with Neural Lexicalization and Big Training Data

Abstract: We study the impact of big models (in terms of the degree of lexicalization) and big data (in terms of the training corpus size) on dependency grammar induction. We experimented with L-DMV, a lexicalized version of Dependency Model with Valence (Klein and Manning, 2004) and L-NDMV, our lexicalized extension of the Neural Dependency Model with Valence (Jiang et al., 2016). We find that L-DMV only benefits from very small degrees of lexicalization and moderate sizes of training corpora. L-NDMV can benefit from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 10 publications
(17 reference statements)
0
21
0
1
Order By: Relevance
“…Recent work has sought to take advantage of word embeddings in unsupervised generative models with alternate approaches (Lin et al, 2015;Tran et al, 2016;Jiang et al, 2016;Han et al, 2017). Lin et al (2015) build an HMM with Gaussian emissions on observed word embeddings, but they do not attempt to learn new embeddings.…”
Section: Syntax Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent work has sought to take advantage of word embeddings in unsupervised generative models with alternate approaches (Lin et al, 2015;Tran et al, 2016;Jiang et al, 2016;Han et al, 2017). Lin et al (2015) build an HMM with Gaussian emissions on observed word embeddings, but they do not attempt to learn new embeddings.…”
Section: Syntax Modelmentioning
confidence: 99%
“…w/ gold POS tags (for reference only) DMV (Klein and Manning, 2004) 55.1 39.7 UR-A E-DMV (Tu and Honavar, 2012) 71.4 57.0 MaxEnc (Le and Zuidema, 2015) 73.2 65.8 Neural E-DMV (Jiang et al, 2016) 72.5 57.6 CRFAE (Cai et al, 2017) 71.7 55.7 L-NDMV (Big training data) (Han et al, 2017) 77.2 63.2 Table 2: Directed dependency accuracy on section 23 of WSJ, evaluating on sentences of length 10 and all lengths. Starred entries ( * ) denote that the system benefits from additional punctuation-based constraints.…”
Section: Unsupervised Dependency Parsing Without Gold Pos Tagsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other work has used neural parameterization for structured models, such as dependency models(Han et al, 2017), hidden semi-Markov models(Wiseman et al, 2018), and context free grammars(Kim et al, 2019).…”
mentioning
confidence: 99%